Cardiomyopathy with Acute Rheumatic Fever in Children: A Case Report - Ni Gusti Ayu Putu Lestari Santika Dewi; Gede Aditya (HM Publisher, 2023)
Cardiomyopathy is defined as a disease of the myocardium that can cause cardiac dysfunction. The complication of this condition usually can manifest in heart failure, arrhythmia, and even sudden death. This study will describe a rare case of cardiomyopathy with acute rheumatic fever in children. In this study, a girl aged 11 years and 2 months with no history of heart disease was admitted to the hospital with congestive heart failure due to cardiomyopathy and acute rheumatic fever. Acute rheumatic fever is diagnosed based on the presence of carditis, high erythrocyte sedimentation rate, and positive antistreptolysin titer-O (ASTO). Cardiomyopathy is diagnosed by echocardiography. The prognosis of this patient is poor due to poor left ventricular function. In conclusion, patients with clinical features of ARF/RHD should be promptly treated and referred for definite diagnosis and long-term management to limit the extent of heart damage.